Formulation and evaluation of virgin coconut oil (VCO) lotion: Effect of variation in emulsifier type and concentration - Amaliyah, Putri Rizqi; Mardawati, Efri; Pareira Prawiranegara, Boy Macklin (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
Indonesia is a tropical country rich in agricultural commodities, such as coconut. One of the derived products from coconut is virgin coconut oil (VCO), which widely used as ingredient in cosmetic lotion products. This study aimed to evaluate the effects of variations in the addition of emulsifiers to VCO cream lotion. Two emulsifiers were used, including Tween 80 and Span 80 with concentrations of 5% without essential oil, 5%, 4%, 3%, and 2%. Quality parameters analyzed were homogeneity, specific gravity, stability, pH, and organoleptic. The data were statistically analyzed using the Kruskall-Wallis test. The results showed that Tween 80 and Span 80 emulsifiers significantly affected physicochemical and organoleptic characteristics, except pH value. The selected best formulation was  cream lotion with the addition of 2% emulsifier formulation. This VCO lotion had a quality value according to SNI 16-4399-1996 and had organoleptic characteristics most preferred by the panelists.